2014
DOI: 10.1583/14-4734mr.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Peripheral Fractional Flow Reserve in Isolated Iliac Artery Stenosis: A Comparison With the Post-Exercise Ankle-Brachial Index

Abstract: Measuring p-FFR appears to be a feasible and safe procedure, and there is a significant linear correlation between post-exercise ABI and p-FFR in aortoiliac lesions. The p-FFR was more accurate than a peak-to-peak pressure gradient in assessing the physiological significance of a stenosis. Though larger studies are required, p-FFR might be used to physiologically assess stenosis in PAD patients with isolated aortoiliac lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…The cut-off of mean resting gradient to determine whether or not the stenosis is significant is discussed ranging from 5 ( 34 ) to 10 mm Hg ( 35 ). The peripheral fractional flow reserve (p-FFR), which is defined as the ratio of the mean pressure distal to the stenosis to the mean aortic pressure at hyperemia, could also be a valuable test ( 36 38 ).…”
Section: Strategies and Evidencesmentioning
confidence: 99%
“…The cut-off of mean resting gradient to determine whether or not the stenosis is significant is discussed ranging from 5 ( 34 ) to 10 mm Hg ( 35 ). The peripheral fractional flow reserve (p-FFR), which is defined as the ratio of the mean pressure distal to the stenosis to the mean aortic pressure at hyperemia, could also be a valuable test ( 36 38 ).…”
Section: Strategies and Evidencesmentioning
confidence: 99%
“…Subsequently, Hioki et al conducted a prospective study to evaluate the clinical utility of PFFR in patients with isolated iliac artery stenosis and correlated this finding with the post-exercise ABI [9]. A total of 16 patients were included in this study.…”
Section: Reviewmentioning
confidence: 99%
“…Another potential solution of problem is the use of peripheral FFR in intermediate stenosis. Hioki et al [ 82 ] found a good correlation of significant strength ( r = 0.857, p < 0.001) between intravascular peripheral FFR with papaverine and postexercise ABI. The correlation between the peak-to-peak pressure gradient in hyperemia and postexercise ABI was also significant, but of relatively milder strength ( r = −0.626, p = 0.013).…”
Section: Functional Assessment Of Intermediate Peripheral Vascularmentioning
confidence: 99%